Syngenta Enogen Corn Fed as Corn Grain and Corn Silage in Diets Containing Corn Coproducts Did Not Enhance Growth Performance of Growing Heifers - M. A. Scilacci; M. A. Johnson; E. C. Titgemeyer; S. P. Montgomery; A. J. Tarpoff; E. D. Watson; W. R. Hollenbeck; Dale Blasi (Kansas Agricultural Experiment Station Research Reports, 2022)
Objective:Evaluate the effect of feeding corn grain and corn silage from Syngenta Enogen corn hybrids (EC; Syngenta Seeds, LLC., Downers Grove, IL) or conventional corn hybrids in diets containing either wet distillers grain (WDG; ICM Biofuels, St. Joseph, MO) or Sweet Bran (WCGF; Cargill Animal Nutrition, Blair, NE) on growth performance in growing cattle. Study Description:Three hundred eighty-four crossbred heifers [initial body weight (BW) = 582 ± 42 lb] were used in a completely randomized design, 81-day receiving and growing study, with a 2 × 2 factorial arrangement of four dietary treatments. Experimental diets were formulated to contain 30% WDG or 30% WCGF on a dry matter (DM) basis and provide 51 megacalories of net energy for gain per 100 lb of DM daily. Diets were fedad libitumonce daily. The Bottom Line:Our results revealed no effect of replacing conventional corn grain and silage with Enogen corn grain and silage on the growth performance of growing cattle, but diets containing WDG resulted in a better gain to feed ratio and average daily gain in growing heifers compared to diets containing WCGF.
Keywords: Enogen corn hybrids; growing cattle; corn coproducts